2020
DOI: 10.3390/cancers12030749
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding microRNAs as Novel Potential Tumor Markers in Testicular Cancer

Abstract: Testicular cancer is an important disease with increasing incidence and a high burden of morbidity and mortality in young men worldwide. Histological examination of the testicular tissue after orchiectomy plays an important role alongside patient history, imaging, clinical presentation and laboratory parameters. Surgical procedures and chemotherapeutic treatment provide a high chance of cure in early stages, though some patients in advanced stages belonging to a poor risk group experience cancer-related death.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 102 publications
(140 reference statements)
2
38
0
Order By: Relevance
“…Future therapies may focus on helping the host clear viruses or decreasing the viral replication by changing the expression of these important ncRNAs. In addition, considering that some ncRNAs of blood will change significantly in the state of disease and have good stability in peripheral circulation, so they have great potential in the field of VMC diagnosis (Regouc et al, 2020 ; Santos et al, 2020 ). In this review, we will mainly describe the potential roles of miRNAs, lncRNAs, and circRNAs in the pathogenesis, diagnosis, and treatment of CVB3-induced viral myocarditis.…”
Section: Introductionmentioning
confidence: 99%
“…Future therapies may focus on helping the host clear viruses or decreasing the viral replication by changing the expression of these important ncRNAs. In addition, considering that some ncRNAs of blood will change significantly in the state of disease and have good stability in peripheral circulation, so they have great potential in the field of VMC diagnosis (Regouc et al, 2020 ; Santos et al, 2020 ). In this review, we will mainly describe the potential roles of miRNAs, lncRNAs, and circRNAs in the pathogenesis, diagnosis, and treatment of CVB3-induced viral myocarditis.…”
Section: Introductionmentioning
confidence: 99%
“…By taking advantage of this integrated network analysis, more immunotherapy targets for seminoma could be identified and clinically applied [ 39 ]. Emerging evidence has shown that non-coding RNA biomarkers play important roles in various human diseases including seminoma [ 40 ]. With the rapid development of computational prediction models, Chen et al proposed several innovative prediction models to identify non-coding RNA biomarkers correlated with human diseases [ 41 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In TC, noncoding RNAs have already been investigated in regards to their involvement in pathogenesis and their potential utility as clinical biomarkers [197,198]. The fact that patients with TC show great response to cisplatin-based chemotherapy may be a reason why data on lncRNAs in the development of chemoresistance is extremely limited.…”
Section: Lncrnas and Drug Resistance In Testicular Cancermentioning
confidence: 99%